(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article analyzed the results of the work carried out in Uzbekistan on the impact of demographic changes on the management of the rural labor market, studied and highlighted current tasks and problems. proposals and recommendations on the impact of demographic changes on rural labour market management are also given.